Quercetin-Induced Lifespan Extension in Podospora anserina Requires Methylation of the Flavonoid by the O-Methyltransferase PaMTH1 - Warnsmann, Verena; Hainbuch, Saskia; Osiewacz, Heinz D. (Frontiers in Genetics, 2018)
Quercetin is a flavonoid that is ubiquitously found in vegetables and fruits. Like other flavonoids, it is active in balancing cellular reactive oxygen species (ROS) levels and has a cyto-protective function. Previously, a link between ROS balancing, aging and the activity of O-methyltransferases was reported in different organisms including the aging model Podospora anserina. Here we describe a role of the S-adenosylmethionine-dependent O-methyltransferase PaMTH1 in quercetin-induced lifespan extension. We found that effects of quercetin treatment depend on the methylation state of the flavonoid. Specifically, we observed that quercetin treatment increases the lifespan of the wild type but not of the PaMth1 deletion mutant. The lifespan increasing effect is not associated with effects of quercetin on mitochondrial respiration or ROS-levels but linked to the induction of the PaMth1 gene. Overall, our data demonstrate a novel role of O-methyltransferase in quercetin-induced longevity and identify the underlying pathway as part of a network of longevity assurance pathways with the perspective to intervene into mechanisms of biological aging.